Status Hadith La Wasiyyah li Warith menurut Imam al-Shafi’iy - Imam Supriyadi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: This article backdrop of, first, how's the views of ‎Imam al-Shafi'iy of the position of the hadith